Dirty dances: academia-industry relations in Russia - Olga Bychkova; Anna Chernysh; Evgeniya Popova (Triple Helix, 2015)
Many commercially successful innovations are now arising from basic research carried out at universities. The boundary between pure science and applied research is blurred. In this context, governments worldwide have been promoting the concept of synergy between basic research carried out in academic institutions and applied research in the commercial sector. By applying different models they are trying to establish the most efficient way of facilitating this relationship with funding from the private sector. In this article, we have explored the case of Russia and overviewed the effects of 'innovation enforcement' policy developed by the Russian government in the late 2000s. As our case demonstrates, the outcome of such a policy is rather negative. However, there are also some positive side effects of the current Russian public policy. One example is the practice of the shared-used equipment. It allows developing trust between university-private company and results in mutually beneficial partnership. Moreover, it stimulates changes in industrial vision of the academic partner. Hence, in some cases, the policy of 'innovation by coercion' can have positive outcomes for it forces academia and industry to see joint collaborations more as a help rather than as a hindrance.
Keywords: O38; 330; Innovation; Public policy; Russian studies; University-industry-government relations